2023
DOI: 10.1002/sd.2527
|View full text |Cite
|
Sign up to set email alerts
|

Does industry 5.0 model optimize sustainable performance of Agri‐enterprises? Real‐time investigation from the realm of stakeholder theory and domain

Abstract: The research on Industry 5.0 (i5.0) is relatively new and emerging therefore professionals are still striving to reveal its influence globally. This study investigates the impact of industry 5.0 to comprehend the insights into how it optimizes the sustainable performance (STP) within three core streams, that is, economic, environmental, and social perspectives from the realm of stakeholder theory within the Chinese agricultural industry. The results stated that i5.0 positively affects the STP of Agri-enterpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…The current values for both NFI and SRMR are reported in Table 6 which are 0.941 for NFI and 0.0124 for SRMR. These techniques adopting SEM and supporting methods are consistent with previous studies where academic scholars, practitioners, and policy developers used similar approaches (Ahmad et al, 2023;Guo et al, 2023;Waheed & Yang, 2019;Wang et al, 2022). a smaller connection (Benesty et al, 2009).…”
Section: Methods For Data Analysissupporting
confidence: 86%
“…The current values for both NFI and SRMR are reported in Table 6 which are 0.941 for NFI and 0.0124 for SRMR. These techniques adopting SEM and supporting methods are consistent with previous studies where academic scholars, practitioners, and policy developers used similar approaches (Ahmad et al, 2023;Guo et al, 2023;Waheed & Yang, 2019;Wang et al, 2022). a smaller connection (Benesty et al, 2009).…”
Section: Methods For Data Analysissupporting
confidence: 86%
“…Figure 3 highlights the noteworthy similarity in the microeconomic goals of Industry 5.0 when compared to Industry 4.0. Scholars suggest that, within the context of Industry 5.0, the advancement of prosperity and growth hinges upon corporations' financial success and economic efficiency (Guo et al, 2023;Waheed et al, 2022). Achieving this necessitates leveraging advanced technologies to enhance the management of logistics and material flow, streamline operations, and boost workforce productivity (Turner and Oyekan, 2023).…”
Section: Economic Valuesmentioning
confidence: 99%
“…The evidence mapping delineates waste reduction as the preeminent microenvironmental advantage of Industry 5.0 for corporations (Guo et al, 2023). Industry 5.0 offers a multifaceted pathway to waste reduction within corporations through its transformative technologies and principles.…”
Section: Environmental Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The i5.0 model helps to promote collaboration with stakeholders, improve SSP, bring transparency in operations, enhance resource efficiency, and improve customization (Dwivedi et al, 2023; Ghobakhloo, Iranmanesh, Morales, et al, 2022; Leng et al, 2022). Moreover, the impact of recent industrial models both i4.0 and i5.0 was determined by researchers to furnish insights into industrialization models in terms of the different domains of SSP such as social, economic, and environmental perspectives (Atif, 2023; Guo et al, 2023). For instance, a study confirmed a positive connection between industrial models and social perspectives from developed nations other than the industrial sector (Ghobakhloo, Iranmanesh, Mubarak, et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%